Propagação de variedades de caramboleira por estaquia herbácea - Nacata, Guilherme [UNESP]; Andrade, Renata Aparecida De [UNESP]; Jasper, Samir Paulo; Prata, Rodrigo Salgado [UNESP] (Sociedade Brasileira de Fruticultura, 2014)
Aiming to evaluate the propagation of three varieties of star fruit by cutting in function of the dose of growth regulator (indolbutiric acid - IBA) used in the treatment of cuttings, this research was realized. Were used apical herbaceous cuttings, being the experiment conducted in intermittent mist chamber, located in lathouse conditions (50% brightness). The cuttings of the varieties B10, Hart and Golden Star received the IBA treatment at doses 100, 200 and 400 mg L-1 (slow immersion) and doses in 1,000, 3,000 and 5000 mg.L-1 (rapid immersion) more control treatment (0 mg L-1 IBA). The evaluations, 90 days after the cutting, were about: percentages of survival, callus and rooting, average number of roots per cutting and mean root length (cm). The experimental design was completely randomized with four replicates per treatment and 10 cuttings in each one, in factorial 3x7 (varieties x IBA). For purposes of analysis, percentage data were transformed into arcsin and subjected to analysis of variance and the means by Tukey test at 5% of probability. By the results obtained in this research, there is no need for treatment the cutting of star fruit with growth regulator (IBA). The variety Golden Star showed the best results, followed by Hart and B10.

Realizou-se o presente trabalho objetivando avaliar a propagação de três variedades de caramboleira por estaquia em função da dose de regulador de crescimento (ácido indolbutírico - AIB), empregada no tratamento das estacas. Foram utilizadas estacas herbáceas apicais, sendo o experimento conduzido em câmara de nebulização intermitente, localizada em condições de ripado (50% de luminosidade). As estacas das variedades B10, Hart e Golden Star receberam o tratamento com AIB, nas doses de 100; 200 e 400 mg.L-1 (imersäo lenta) e nas doses de 1.000, 3.000 e 5.000 mg.L-1 (imersäo rápida), mais tratamento-testemunha (0 mg.L-1 de AIB). As avaliações, 90 dias após a estaquia, foram quanto: porcentagens de sobrevivência, calejamento e enraizamento; número médio de raízes por estaca e comprimento médio das raízes (cm). O delineamento experimental foi o inteiramente casualizado, com quatro repetições por tratamento, compostas por 10 estacas, analisado em fatorial 3 x 7 (variedades x AIB). Conforme resultados obtidos neste trabalho, näo há necessidade do tratamento das estacas de caramboleira com regulador de crescimento (AIB). A variedade Golden Star mostrou melhores resultados, seguida pela Hart e B10.
Propagation of three varieties of star fruit by herbaceous cutting
Keywords: Averrhoa carambola L.; propagação vegetativa; ácido indolbutírico; Averrhoa carambola L.; vegetative propagation; indolbutiric acid